ANALISIS BIAYA VOLUME LABA MULTI-PRODUK UNTUK PERENCANAAN LABA JANGKA PENDEK BIJIMERAH COFFEE AND ROASTERY - Mokoginta, Mia Istiana; Sondakh, Jullie J.; Budiarso, Novi S. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Each Company has the same goal to earn profit from the products and services offered. Cost volume profit analysis is used by managers for decision making, planning and as well as the implementation of a cost grouping for short-term profit planning purposes. This study was conducted on Bijimera Coffee and Roastery. The purpose of this study is to know the short-term profit planning on Bijimera Coffee and Roastery by using cost volume profit analysis and multiproduct cost volume profit analysis. Research method used by researcher is descriptive quantitative research type by using break even point analysis, contribution margin, margin of safety, operating leverage and sales mix analysis. Results and conclusions from the study are the contribution margin package of the two product mix is Rp. 700,846.26. The break-even point in the unit of the product mix is 546.74 kg for Bogani Bland product and 234.32 kg for Robusta Modayag product. The company breaks even when the total sales of both products is Rp. 110,128,860. By using the cost volume profit analysis, the company will more easily predict management decisions for the future. In addition, the company can prevent things that adversely affect the company based on the calculation of costs through breakeven analysis, contribution margin, margin of safety, operating leverage and sales mix analysis.Keywords: Cost Volume Profit, Profit Planning, Multiproduct Analysis